Variety of Endoscopic Techniques in the Treatment for Retroduodenal Perforation - S. A. Tarasov; S. V. Novikov; P. A. Yartsev; R. Sh. Bayramov; S. O. Aksenova; A. V. Kachmazova; A. M. Kuzmin (Неотложная медицинская помощь, 2025)
The article presents a clinical observation of successful treatment for retroduodenal perforation (RDP) resulting from conducted retrograde endoscopic examination, papillotomy using a combined minimally invasive treatment method, which included bilioduodenal and pancreatic stenting, endoscopic vacuum therapy (EVT), transluminal drainage. The use of the EVT system together with endoscopic stenting of the biliary and pancreatic ducts made it possible to prevent the development of fatal retroperitoneal phlegmon by actively removing purulent discharge, necrotic tissues from the area of infection, reducing ductal hypertension, which contributed to the delimitation of the process. Transluminal drainage with multiple subsequent transluminal sanation demonstrated a good result in the form of adequate draining, the possibility of performing endoscopic sanitation of the lesion, and further complete regression of the delimited fluid cavity. The use of minimally invasive methods in the treatment for retroduodenal perforation made it possible to avoid the spread and generalization of purulentseptic fatal retroperitoneal complications, and to accelerate the process of successful treatment.